HALO EFFECT IN STUDENTS’ EVALUATIONS OF COMMUNICATION ETHICS IN ACADEMIC INTERACTION: A PHENOMENOLOGICAL STUDY OF KPI STUDENTS - Windari Syntia; Nurhasanah Lubis; Rafi Salim Parinduri; Mona Hardinah (Academic Solution Publisher, 2026)
This study examines the influence of the halo effect on students’ evaluations of communication ethics in academic interactions among students of the Islamic Communication and Broadcasting (KPI) study program. The halo effect refers to students’ tendency to form initial judgments about lecturers based on first impressions such as appearance, tone of voice, and presentation style. This research employs a qualitative phenomenological approach to explore students’ lived experiences in academic communication. The participants consisted of ten KPI students selected through purposive sampling. Data were collected through in-depth open-ended interviews and analyzed using the phenomenological analysis procedure proposed by Moustakas, which includes horizontalization, thematic clustering, and synthesis of meanings. The findings reveal that the halo effect shapes students’ perceptions of lecturers’ credibility, competence, and communication ethics, particularly during the early stage of academic interaction. However, these perceptions tend to evolve through continued learning experiences. The study contributes to educational communication research by demonstrating how perceptual bias influences the evaluation of communication ethics in higher education.